Lung Tumor Induction by 26-week Dermal Application of 1, 2-Dichloroethane in CB6F1-Tg rasH2 Mice. (April 2017) - Suguro, Mayuko; Numano, Takamasa; Kawabe, Mayumi; Doi, Yuko; Imai, Norio; Mera, Yukinori; Tamano, Seiko
Short-term alternatives to traditional 2-year carcinogenic studies in rodents are being actively pursued. Recently, a 26-week short-term carcinogenicity study using CB6F1-Tg rasH2@Jcl (rasH2) mice has become a worldwide standard for the evaluation of chemical carcinogenesis. However, an acceptable short-term carcinogenic study model for dermally applied products is still lacking. To investigate the suitability of using the rasH2 mouse to test carcinogenic potential, 1, 2-dichloroethane (1, 2-DCE) was dermally applied to rasH2 mice: 1, 2-DCE is a known carcinogen that causes lung bronchiolo-alveolar adenomas and adenocarcinomas when administered topically, orally, or by inhalation exposure; 1, 2-DCE at a dose level of 126 mg/mouse in 200 μl acetone or acetone alone (vehicle control) was applied to the dorsal skin of 10 mice of each sex 3 times a week for 26 weeks. As a positive control, 10 mice of each sex received a single intraperitoneal injection of 75 mg/kg of N -methyl- N -nitrosourea. Bronchiolo-alveolar adenomas and adenocarcinomas were significantly increased in 1, 2-DCE-treated rasH2 mice of both sexes, and bronchiolo-alveolar hyperplasias were significantly increased in female mice. Overall, almost all mice of each sex developed adenomas and/or adenocarcinomas with 100% of female rasH2 mice developing bronchiolo-alveolar adenocarcinomas.